2020
DOI: 10.1093/bioinformatics/btaa563
|View full text |Cite
|
Sign up to set email alerts
|

Screening novel drug candidates for Alzheimer’s disease by an integrated network and transcriptome analysis

Abstract: Motivation Alzheimer’s disease (AD) is a serious degenerative brain disease and the most common cause of dementia. The current available drugs for AD provide symptomatic benefit, but there is no effective drug to cure the disease. The emergence of large-scale genomic, pharmacological data provides new opportunities for drug discovery and drug repositioning as a promising strategy in searching novel drug for AD. Results In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 60 publications
1
25
0
Order By: Relevance
“…To further determine the potential drug targets of key IDD genes, following Wang et al [ 18 ], we determined the network distance between these 3 key genes and 5490 drugs on DrugBank ( Figure 6(a) ), and found that the distance between the three key genes and the drug was shorter than that of the random background. A total of two drugs were determined according to a global FDR < 0.05 ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further determine the potential drug targets of key IDD genes, following Wang et al [ 18 ], we determined the network distance between these 3 key genes and 5490 drugs on DrugBank ( Figure 6(a) ), and found that the distance between the three key genes and the drug was shorter than that of the random background. A total of two drugs were determined according to a global FDR < 0.05 ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…These drug-target genes and IDDG genes were mapped to the STRING V11.0 [ 16 ] database to obtain gene interaction information, and a drug-gene-IDDG network was constructed. As previously described by Wang et al [ 18 ], the shortest path of drugs to IDDG was calculated for identifying potentially related drugs to IDDG.…”
Section: Methodsmentioning
confidence: 99%
“…Genes (nodes) with interaction (links) constructed a network graph of PPI, while the interaction between two nodes was undirected and unweighted. Here, a proximity score was defined by the average shortest path length between the drug target genes and their nearest disease proteins in the context of PPI to quantify the therapeutic effect of drugs [28,29]. Given the set of COVID-19 related genes sourced from SARS-CoV-2 proteins (S), the group of drug target genes (T), the shortest distance between two genes in the PPI network d(s, t) where s∈S and t∈T (Equation (1)),…”
Section: Network-based Proximity Between Drugs and Covid-19mentioning
confidence: 99%
“…To observe potential drugs targeting LRM-CAD, 5,490 druggene interaction data were obtained from Drugbank (31) using the method previously described by Peng et al (32). These proteins and genes in LRM-CAD were mapped to the Search Tool for the Retrieval of Interacting Genes/Proteins (STRING) database ( 33) to construct drug-protein and protein-protein interaction network (DPPI) and used to define the degree of node of LRM-CAD-related gene set in PPI, T, and drug target gene set.…”
Section: Identification Of Potential Drugs Targeting Lrm-cadmentioning
confidence: 99%